Special measures for child witnesses: a socio-legal study of criminal procedure reform - Cooper, Debbie (2010)
This thesis is a socio-legal study of police and prosecutorial decision-making in the context of special measures support for child witnesses in criminal proceedings. It presents the findings of an empirical research project conducted with the Crown Prosecution Service which examined the implementation of Part II of the Youth Justice and Criminal Evidence Act 1999. Under that Act children may be assisted to testify in criminal proceedings though any feasible combination of: video-recorded evidence; live television link; screens; communication aids; intermediaries; and giving evidence in private. Using a small-scale, primarily qualitative, study involving semi-structured interviews with Crown Prosecutors, this thesis investigates how the attitudes, beliefs, motivations and work practices of the police and prosecutors affect the provision of special measures to children. It does so in the context of a highly directive legal framework which purports to curtail prosecutorial and judicial discretion. The thesis explores the problems that child witnesses encounter within the criminal justice system and the legislative and policy response to their difficulties. It then presents the findings of the current research study in relation to, first, the video-interviewing patterns of police officers and, second, the rate of prosecutors’ applications for special measures. In addition to the statistical data, the thesis explores prosecutors’ own reflective accounts of the factors which shape police and prosecutors’ decision-making. The thesis concludes that where the rules on special measures are highly prescriptive, we have witnessed a radical expansion in their use for children, but that the rigid system has drawbacks which raise pressure for reform. Reform proposals must be carefully considered in the light of infrastructural weaknesses in inter-agency liaison and information-management identified in this thesis. We might also be wary that reform will undermine the criminal justice system’s recently consolidated cultural acceptance of special measures for child witnesses.